Strategic behavior in IEAs: When and why countries joined the Kyoto Protocol - Christian Almer; Ralph Winkler (University of Bern, Department of Economics, 2010)
We empirically analyze the formation of international environmental agreements within a political economy framework. We develop a theoretical model of state dependent net benefits of ratification predicting (i) strategic behavior with respect to the timing of ratification and (ii) that ratification per se is not necessarily a stronger signal of support compared to signature. Analyzing the signature and ratification process via generalized binary and ordered response models, we find significant evidence for our theoretical predictions. In addition, we show that a wide selection of determinants including economic and political factors influences the decision whether to sign and when to ratify.
Keywords: Q54; F53; C25; 330; Climate Change; Generalized Response Models; International Environmental Agreements; Kyoto Protocol; Klimawandel; Umweltabkommen; Politische Entscheidung; Wirtschaftswissenschaft; Theorie